1998
DOI: 10.1136/gut.43.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Oncological implications of RET gene mutations in Hirschsprung’s disease

Abstract: Background-Germline mutations of the RET proto-oncogene identical to those found in the tumour predisposition syndrome multiple endocrine neoplasia type 2A (MEN2A), were detected in 2.5-5% of sporadic and familial cases of Hirschsprung's disease. Some patients with Hirschsprung's disease may therefore be exposed to a highly increased risk of tumours. Aims-To define clinical use of RET gene testing in Hirschsprung's disease and related patient management from an oncological point of view. Methods-Sixty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…No case that shows two-nucleotide alteration in one codon of the RET gene was previously reported, although some cases that have two codons with onenucleotide alteration in the RET gene were reported. 27 In addition, the present case showed no nucleotide alterations at polymorphic codons in the RET gene that may affect the development of HSCR. 34 -38 Germline mutations in several genes including GDNF, neurturin, endothelin receptor B, endothelin-3, SOX10, endothelin-converting enzyme 1, and ZFHX1B were reported in HSCR patients.…”
Section: Discussionmentioning
confidence: 93%
“…No case that shows two-nucleotide alteration in one codon of the RET gene was previously reported, although some cases that have two codons with onenucleotide alteration in the RET gene were reported. 27 In addition, the present case showed no nucleotide alterations at polymorphic codons in the RET gene that may affect the development of HSCR. 34 -38 Germline mutations in several genes including GDNF, neurturin, endothelin receptor B, endothelin-3, SOX10, endothelin-converting enzyme 1, and ZFHX1B were reported in HSCR patients.…”
Section: Discussionmentioning
confidence: 93%
“…Activating RET mutations have been found previously in HSCR but were mostly found in the context of MEN2/familial MTC (eg, p.Cys610/618/620). 9 For all activating RET mutations, found in HSCR patients, it was shown that the mutant protein besides being activated, also results in a disturbed glycosylation. Our analysis did not show any difference in the glycosylation status.…”
Section: Rare Ret Variantsmentioning
confidence: 99%
“…The majority of patients with gain-of-function mutations suffered, besides HSCR, also from multiple endocrine neoplasia type 2 A (MEN2A) or familial medullary thyroid carcinoma (MTC). 9 Not many studies, however, determined the functional consequences these mutations really have on the encoded RET protein. [10][11][12] Most reports stated their classification of pathogenicity only on in silico predictions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these cancer syndromes, which are caused by a germline mutation and associate with MTC, somatic gene rearrangements of the RET gene are associated with papillary thyroid cancer (Grieco et al 1990). The incidence of MTC has been reported to vary between 2.5 and 5% among HD patients (Decker et al 1998, Sijmons et al 1998, Pakarinen et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Only mutations in codons 609, 611, 618, and 620 of exon 10 are known to co-segregate with HD and MEN syndromes (Mulligan et al 1994a,b, Romeo et al 1998, Sijmons et al 1998, Nishikawa et al 2003. Mutations in codon 791 of the RET gene are suggested to be weak or nonpathogenic mutations for MEN2A and familial medullary thyroid carcinoma (FMTC) (Frank-Raue et al 2008, Erlic et al 2010.…”
Section: Introductionmentioning
confidence: 99%